KEDUDUKAN EKSEKUSI HAK TANGGUNGAN BERDASARKAN GROSSE AKTA PENGAKUAN UTANG - Putra, Moch. Rizky Adi Pratama; Wahjoeono, Dipo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Based on the results of the study, it was concluded that the grosse execution of the debt acknowledgment deed is not an act of execution by a court against a court decision that has obtained permanent legal force. On the contrary, the execution is an action taken to fulfill the contents of the agreement made by the parties, and in order for the grosse deed of acknowledgment of debt to have executive power, it must meet the requirements of validity. Factors that may impede the execution of grosse acknowledgment of debt include factors of legal substance, law enforcers, interested parties, as well as formal and material factors. The execution process must comply with the procedures, conditions, and stages that have been determined, namely warning (aanmaning), determination, and minutes of execution